-8(x+7)+60=9-9x

Simple and best practice solution for -8(x+7)+60=9-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(x+7)+60=9-9x equation:


Simplifying
-8(x + 7) + 60 = 9 + -9x

Reorder the terms:
-8(7 + x) + 60 = 9 + -9x
(7 * -8 + x * -8) + 60 = 9 + -9x
(-56 + -8x) + 60 = 9 + -9x

Reorder the terms:
-56 + 60 + -8x = 9 + -9x

Combine like terms: -56 + 60 = 4
4 + -8x = 9 + -9x

Solving
4 + -8x = 9 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
4 + -8x + 9x = 9 + -9x + 9x

Combine like terms: -8x + 9x = 1x
4 + 1x = 9 + -9x + 9x

Combine like terms: -9x + 9x = 0
4 + 1x = 9 + 0
4 + 1x = 9

Add '-4' to each side of the equation.
4 + -4 + 1x = 9 + -4

Combine like terms: 4 + -4 = 0
0 + 1x = 9 + -4
1x = 9 + -4

Combine like terms: 9 + -4 = 5
1x = 5

Divide each side by '1'.
x = 5

Simplifying
x = 5

See similar equations:

| 4b-14b-17=65 | | 5y-4=4y-2 | | 7r=(-5r)+144 | | 2n+3=15-n | | 10(0)-5y=20 | | 10x-5(0)=20 | | 35+(25+r)=r | | (y^2)-2y=(x^3)+2(x^2)+2 | | 15g+3g-17g+g+1=15 | | 3/9*23+(7*8)= | | 20x-4y=-12 | | 3x+21y=21 | | 3(x+7)-3=53-2x | | 4(3x)=512 | | -8q+-9+-q+8=-10 | | -6+4x=-9 | | t(3-4t)=o | | 3x+22=30 | | 4m-4m+3m+1=10 | | 4q-(2q+6)=5-(2q-8) | | y+4=3(x+2) | | 19a+-20a=-4 | | 0.05x+0.12(x+5000)=94.0 | | m(m+12)= | | 4m^2+8m+10=0 | | 1444=-12(x+5) | | 42=x^2-13x | | 80=8f | | y=8+7cos(3x) | | 12y+32= | | 2h-1000=4400 | | 4x^2+15=32x |

Equations solver categories